Eksplorasi Customer Experience dan Fasilitas sebagai Faktor Penentu Minat Berkunjung Kembali Di Desa Wisata - Fahimah, Mar'atul; Rasyid, Raihan (Forum Kerjasama Pendidikan Tinggi, 2025)
Indonesia holds significant potential in the tourism sector due to its rich cultural and natural diversity, including tourist villages that offer unique experiences for visitors. This study aims to examine the influence of customer experience and facilities on revisit intention at Pandan Sili Tourism Village, Jombang. The research employs a quantitative method with data collected through questionnaires. The results of the analysis indicate that customer experience and facilities have a positive and significant impact on revisit intention. Customer experience, encompassing service quality, comfort, and satisfaction, plays a substantial role in creating a lasting impression and enhancing tourists' desire to return. Adequate facilities, such as accessibility, cleanliness, and supporting infrastructure, also play a crucial role in improving visitor comfort. Simultaneously, these two variables contribute significantly, with an R-square value of 0.850, explaining 85% of the variation in revisit intention. These findings are consistent with previous studies, affirming that both customer experience and facilities play a critical role in increasing visitors' intention to return to tourist destinations.